Smoking Habit and Clinico-Biological Parameters of Breast Cancer - A Ruibal; P Aguiar; P Menéndez; J I Arias; A Gonzalez-Sistal; M Herranz (Journal of Tobacco Stimulated Diseases - Peertechz Publications, 2017)
Introduction: The aim of this study was to analyse the possible associations between smoking habit and some clinico-biological parameters of breast infi ltrating ductal carcinomas (IDCs).Material and Methods: The study group included included 291 females with IDC who had undergone no prior treatment. Out of them, 48 were current smoking, 11 quit smoking and 232 never smoking. All were studied at the same Breast Cancer Unit. Age, tumor size, axillary lymph node involvement (N), distant metastasis (M) and histological grade (HG), as well as the immunohistochemical expression of estrogen receptor (ER), progesterone receptor (PgR), Ki67, p53, bcl2 and androgen receptor (AR) were analyzed Also, we dose the serum levels of CEA and CA15.3. We can follow up 276 patients during a period of time which ranged between 8 and 240 months (83,3+/-51,8; median 84 months). Results: IDCs of smoking habit subgroup had lower age than nonsmoking habit subgroup and were more frequently bcl-2+ (p 0,083). There were not differences in the other clinico-biological parameters as well as in the follow-up considering recurrences and deaths due to the tumor. Likewise, age of ex-smoking habit subgroup was similar to that observed in active smoking habit subgroup, and lower than that observed in nonsmoking habit subgroup (p: 0,003). Smokers women showed more frequently history of contraceptives intake (26,4% vs 7,8% ; p<0,001). When we considered the molecular subtypes of IDCs, we not observed any statistically difference; nevertheless, when we analyzed current and quit versus never smoking patients, , we noted than luminal B subtype was less frequent in those (p: 0,068) and the tumors were more frequent bcl-2 positive (p:0,048) than never smoking subgroup.Conclusion: Our results led us to the following: 1) Women with IDCs and smoking habit had lower age and the tumors were more frequently bcl2 positive than never smoking habit; 2) age of ex smoking habit subgroup was similar to that observed in active smoking habit subgroup, and lower than that observed in nonsmoking habit subgroup ; 3) in smoking/ex-smoking women luminal B molecular subtype was less frequent than in nonsmoking women.